FINANCIAL STATEMENT FRAUD AND FIRM PERFORMANCE: EMPIRICAL EVIDENCE FROM INDONESIA - Rossy Pratiwy Sihombing (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Fraudulent financial reporting is an intentional misstatement of the financialstatements, which is the incorrect representation intentionally used to manipulatethe decision of stakeholders by ensuring that they make their decision based onincorrect information. This study examines factors affecting the likelihood offinancial statement fraud occurrences and differences between fraudulent and nonfraudulent companies listed in Indonesia Stock Exchange with respect to thecompany’s profitability over the period 2010 to 2018. Empirical results indicatethat the ratio of current assets to total assets, long-term debt to total equity, totalsales to total equity, and the cost of goods sold to sales have significant impact onaffecting the likelihood of financial statement fraud. Based on the propensity scorematching using cross-sectional data, the study finds that profitability has nosignificant difference between fraudulent and non-fraudulent companies